Art + science now - Wilson, Stephen (London : Thames & Hudson, 2012)
Offers an overview of the art being made at the scientific research. This title shows how some of the world's most dynamic art is being produced not in museums, galleries and studios but in the laboratory, where artists probe cultural, philosophical and social questions connected with scientific and technological advances.
Originally published: 2010.
boek